Treatment of the Aortic Valve in the Modern Era—A Review of TAVR vs. SAVR - Albert Dweck; Brandon E. Ferrell; Daniel Guttman; Stephen M. Spindel; Tadahisa Sugiura (Surgeries)
Aortic stenosis (AS) is the most common valve disease in developed countries, with severe cases traditionally managed through surgical aortic valve replacement (SAVR). More recently, transcatheter aortic valve replacement (TAVR) has been used as a less invasive alternative, especially for patients deemed high-risk for surgery. This review aims to compare SAVR and TAVR by examining the efficacy, patient selection criteria, complications, and evolving guidelines. SAVR is the preferred option for patients at low surgical risk or with anatomical challenges unsuitable for TAVR. It offers well-documented durability and favorable long-term survival. Conversely, TAVR has gained acceptance for intermediate- and high-risk patients, with shorter recovery times and reduced immediate postoperative risks. However, questions surrounding its long-term durability in younger populations persist. Complications differ between the approaches, with TAVR associated with vascular access injuries and arrhythmic events, while SAVR presents risks tied to open surgery. As clinical guidelines evolve, patient age, comorbidities, and life expectancy play critical roles in determining the optimal intervention. This review highlights the need for tailored treatment approaches, given the expanding indications and evolving evidence for both SAVR and TAVR in AS management.